2009 IEEE International Conference on Acoustics, Speech and Signal Processing 2009
DOI: 10.1109/icassp.2009.4960056
|View full text |Cite
|
Sign up to set email alerts
|

On the role of localization cues in binaural segregation of reverberant speech

Abstract: Approaches to binaural and stereo speech segregation have often assumed that localization information can be used as a primary cue to achieve segregation of a target signal. Results produced by these systems degrade significantly in the presence of room reverberation. In this work, we present an alternative framework to achieve localization of groups of time-frequency units. We show that grouping across time and frequency allows the use of localization as an important cue for sequential grouping of time-freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…In [15], pitch and ITD are used to achieve localization of simultaneous speakers in reverberant environments. Our prior work analyzed the impact of idealized monaural grouping on localization and segregation of speech in reverberant environments [16], and showed that pitch-based monaural grouping can be used to achieve accurate localization of multiple sources in noisy and reverberant environments [17].…”
mentioning
confidence: 99%
“…In [15], pitch and ITD are used to achieve localization of simultaneous speakers in reverberant environments. Our prior work analyzed the impact of idealized monaural grouping on localization and segregation of speech in reverberant environments [16], and showed that pitch-based monaural grouping can be used to achieve accurate localization of multiple sources in noisy and reverberant environments [17].…”
mentioning
confidence: 99%